Health Effects of a Farming Program to Foster Community Social Capital of a Temporary Housing Complex of the 2011 Great East Japan Earthquake. (16th February 2015) - Takahashi, Sho; Ishiki, Mikihito; Kondo, Naoki; Ishiki, Aiko; Toriyama, Takeshi; Takahashi, Shuko; Moriyama, Hidenori; Ueno, Masahiro; Shimanuki, Masaaki; Kanno, Toshio; Oki, Tomoharu; Tabata, Kiyoshi
ABSTRACT: Objective: We launched a health promotion program called the Hamarassen ("let's get together") Farm, which provided farming opportunities for the victims of the Great East Japan Earthquake who resided in temporary housing. The aim of this study was to evaluate the effects of this program on physical and mental health in terms of bone mineral density (BMD) and a sense of purpose in life. Methods: Among 39 female participants in whom BMD was evaluated, there were 12 Hamarassen participants, 8 self-farming control subjects, and 19 non-farming control subjects. BMD was measured by calcaneal quantitative ultrasound immediately after the project launch and 5 months later. A sense of purpose in life prior to and 2 months after the project's commencement was measured in 21 additional Hamarassen participants by use of the K-I Scale. Interviews were also conducted to qualitatively evaluate the effects of the Hamarassen program. Results: The mean BMD T-score improved by 0.43 in the Hamarassen group, by 0.33 in the self-farming group, and by 0.06 in the controls (p=0.02). Among the 21 Hamarassen participants in whom mental health was evaluated, the average score for a sense of purpose in life improved from 20.5 to 24.9 (p=0.001). Conclusions: The Hamarassen Farm provided disaster victims with opportunities for social participation, interpersonal interaction, and physical exercise; such opportunities may improve physical and psychosocial well-being. ( Disaster Med Public Health Preparedness . 2015;9:103-110)